2007
DOI: 10.1007/s00442-007-0854-4
|View full text |Cite
|
Sign up to set email alerts
|

Elk browsing increases aboveground growth of water-stressed willows by modifying plant architecture

Abstract: In the northern elk wintering range of Yellowstone National Park, USA, wolf (Canis lupus) removal allowed elk (Cervus elaphus) to overbrowse riparian woody plants, leading to the exclusion of beaver (Castor canadensis) and a subsequent water table decline in many small stream valleys. Reduced elk browsing following wolf reintroduction may or may not facilitate willow (Salix sp.) recovery in these areas. To determine if the effect of elk browsing on willow interacts with that of beaver abandonment, we manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 40 publications
3
36
1
1
Order By: Relevance
“…However, increased availability of water offers a plausible mechanism for these responses for two reasons. Photosynthetic rates of willows on undammed plots with deep water tables were limited by water availability [49], and isotopic analysis of water use by willows adjacent to our plots showed clear positive correlations between height and access to groundwater [24]. Tercek et al [50] observed that tall willows had twice rspb.royalsocietypublishing.org Proc R Soc B 280: 20122977…”
Section: Discussionmentioning
confidence: 99%
“…However, increased availability of water offers a plausible mechanism for these responses for two reasons. Photosynthetic rates of willows on undammed plots with deep water tables were limited by water availability [49], and isotopic analysis of water use by willows adjacent to our plots showed clear positive correlations between height and access to groundwater [24]. Tercek et al [50] observed that tall willows had twice rspb.royalsocietypublishing.org Proc R Soc B 280: 20122977…”
Section: Discussionmentioning
confidence: 99%
“…The August xylem pressure potentials corresponded to an approximate 25% loss of hydraulic conductance in S. geyeriana shoots (Johnston et al 2007). Therefore, the plants experienced considerable late season water stress.…”
Section: Discussionmentioning
confidence: 99%
“…The suppressed willow communities created by heavy elk browsing may have competitively excluded beaver (Baker et al 2005, Hebblewhite et al 2005. Beaver and willow form a symbiotic relationship as beaver use willows for dam building, and the dams raise local water tables and stimulate willow productivity (Lindroth and Bath 1999, Baker et al 2005, Westbrook et al 2006, Johnston et al 2007. Where beavers had historically altered local water tables on the northern range, beaver abandonment was accompanied by channel incision through up to 2 m of alluvial sediments (Wolf et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For resource managers, impacts from ungulates on vegetation are becoming a common management problem [105][106][107][108][109], while options for controlling ungulate populations by slaughter, translocation and reproductive control receive little public and/or government support [110]. Translocation receives the greatest level of public support, but disease concerns have reduced the safety of translocating wildlife [111][112][113][114].…”
Section: Discussionmentioning
confidence: 99%